Intra-Abdominal Solid Organ Injury Management in Pediatrics - Subrumaniam, K; Sakti, Sakti; daliza, Nur; Yan, YW (IIUM Medical Journal Malaysia, 2019)
Abdominal trauma is relatively uncommon in children but can leads to a significant morbidity and mortality in the pediatric population. The abdomen is the third most commonly injured anatomic region in children, after the head and the extremities. The abdomen is the most common site of initially unrecognized fatal injury in traumatized children. We are reporting a case of a child with multiple solid organ injury that was successfully treated non-operatively at our center. We presented a previously healthy 9-month-old girl, presented with fluctuating GCS secondary to motor vehicle accident with borderline hemodynamic stability. She was intubated, blood transfusion commenced and a single inotrope support started. She subsequently diagnosed with grade III liver injury, grade II splenic injury, right grade IV renal injury with large perinephric and retroperitoneal hematoma and moderate hemoperitoneum, a non-displaced left superior pubic rami fracture and cerebral edema on computed tomography (CT). She was admitted to pediatric intensive care unit (PICU). Her intra-abdominal injury injuries were successfully treated conservatively. She required a right chest tube on post trauma day 2, for right hemothorax. The chest tube was removed 3 days later following adequate drainage. She eventually was weaned off from ventilator on post trauma day 11. Feeding was commenced on day 7 of post trauma. She was discharge home well after 3 weeks post trauma with periodical follow up. Conclusion: Pediatric intra-abdominal solid organ injury is relatively uncommon, but a potential source of significant morbidity. Non-operative management is the standard of care for the majority of these injuries, which have shown successful rate more than 95%, although continued hemodynamic instability mandates operative intervention.